The Impacts of Globalization on Inequality in the Post-COVID-19 World: Evidence From China - Cheong, Tsun Se; Wu, Yanrui; Wojewodzki, Michal; Ma, Ning (Frontiers in Public Health, 2021)
Empirical studies suggest that globalization (FDI and international trade) has been greatly affected by the COVID-19 and related anti-pandemic measures imposed by governments worldwide. This paper investigates the impact of globalization on intra-provincial income inequality in China and the data is based on the county level. The findings reveal that FDI is negatively associated with intra-provincial inequality, intra-provincial inequality increases as the primary industry sector (agriculture) declines. The result also finds that the increase in inequality stems not from the development in the tertiary or secondary industry sectors per se, but the unevenness in the distribution of these sectors.